A Negative-Pressure Face-Mounted System Reduces Aerosol Spread during Endonasal Endoscopic Surgery - Gandham, Edmond Jonathan; Goyal-Honavar, Abhijit; Johnson, Latif Rajesh; Gupta, Ankush; Thomas, Regi; Devasahayam, Suresh; Prabhu, Krishna; Chacko, Ari George (Journal of Neurological Surgery Part B: Skull Base, 2022)
Purpose Due to the potential risk of COVID-19 transmission during endonasal surgery, we studied methods to reduce droplet and aerosol generation during these procedures.Methods Droplet spread was assessed using ultraviolet light and a camera that detected fluorescence in the operative field and surgeon's personal protective equipment. Density of aerosols sized <10 µm was measured using a photometric particle counter. We designed a face-mounted negative-pressure mask placed on the patients' face during endoscopic endonasal surgery. Sixteen patients were recruited between October 2020 and March 2021 and randomly assigned to the mask and no-mask groups. We compared droplet spread and aerosols generated in both groups, with copious irrigation and continuous suction during drilling forming the mainstay of surgical technique in all cases.Results Droplet contamination due to direct spillage of fluorescein from the syringe was noted in two patients. Aerosol density rose during sphenoid drilling in both groups, with no significant difference when continuous suction and irrigation were employed (1.27 times vs. 1.07 times the baseline, p = 0.248). Aerosol density rose significantly when suction and irrigation were interrupted in the no-mask group (44.9 times vs. 1.2 times, p = 0.028), which was not seen when the mask was used.Conclusion Aerosol generation increases during drilling in endonasal procedures and is a concern during this pandemic. The use of a rigid suction close to the drill along with copious irrigation is effective in reducing aerosol spread. The use of a negative pressure mask provides additional safety when inadvertent blockage of suction and inadequate irrigation occur.
Keywords: aerosol; droplet; generation; mask; suction; endonasal surgery